Pemanfaatan Aplikasi GeoGebra Mampu Meningkatkan Pemahaman Grafik Fungsi Kuadrat Siswa SMA Negeri 1 Singaraja - Narohita, Gede Alit (SCAD Independent, 2023)
Understanding the characteristics of quadratic function graphs is an essential competency in the mathematics curriculum. However, students often face difficulties when interpreting graphs created manually, as these drawings are frequently inaccurate, less proportional, and time-consuming to produce. Such limitations can reduce students’ motivation and hinder the development of conceptual understanding. The integration of dynamic mathematical software such as GeoGebra offers an effective solution to these challenges. GeoGebra enables teachers to present more precise, engaging, and interactive visualizations of quadratic functions, allowing students to explore algebraic forms and their graphical representations more meaningfully. Through exploration, students are encouraged to observe patterns, test hypotheses, and construct understanding independently in alignment with the scientific approach mandated in the 2013 curriculum. This classroom action research, conducted in two cycles with students of class X MIA 7 SMA Negeri 1 Singaraja, demonstrates that the use of GeoGebra significantly improves students’ comprehension of quadratic function graphs. The results show an increase in both the average learning outcomes and the percentage of mastery from cycle I to cycle II. In conclusion, the implementation of GeoGebra not only enhances visualization and learning efficiency but also strengthens students’ conceptual understanding and engagement with the topic of quadratic functions.